Sustainable Prioritization of Public Asphalt Paved Road Maintenance - Kelvin Lungu Agabu; Chabota Kaliba; Erastus Mishengo Mwanaumo (International Journal of Engineering and Management Research, 2023)
The development of transportation infrastructure is crucial for a country's progress as it enables access to social and economic amenities and acts as a vital link between production and consumption. This is particularly significant for landlocked nations like Zambia, which heavily rely on a wide network of public highways, including both paved and unsurfaced roads. Regardless of their quality and construction, all road surfaces degrade over time due to the combined effects of traffic load and environmental factors. If not properly managed, this can lead to costly repairs and rehabilitation efforts. Government organizations face a dilemma when deciding which public roads to prioritize for maintenance. This follows that the inherent hurdle is competing needs within limited finances for infrastructure development. However, the challenge of road maintenance prioritization can be addressed by adopting a multi-criteria approach. This study aims to address the issue of sustainability and provides insights into which public roads should be given priority for maintenance. The research proposes a comprehensive set of criteria focusing on sustainability and assigns relative importance to them, with emphasis on state of deterioration, emergency function, climate resilience, environment, strategic importance, social considerations, economic factors, and political importance. It suggests that road maintenance decision-making should prioritize sustainability, resilience, and societal well-being, challenging traditional assumptions.